OncoSplicing: an updated database for clinically relevant alternative splicing in 33 human cancers. Issue Volume 50:Issue D1(2022) (23rd September 2021) - Zhang, Yangjun; Yao, Xiangyang; Zhou, Hui; Wu, Xiaoliang; Tian, Jianbo; Zeng, Jin; Yan, Libin; Duan, Chen; Liu, Haoran; Li, Heng; Chen, Ke; Hu, Zhiquan; et al.
Abstract: Alternative splicing (AS) represents a crucial method in mRNA level to regulate gene expression and contributes to the protein complexity. Abnormal splicing has been reported to play roles in several diseases, including cancers. We developed the OncoSplicing database for visualization of survival-associated and differential alternative splicing in 2019. Here, we provide an updated version of OncoSplicing for an integrative view of clinically relevant alternative splicing based on 122 423 AS events across 33 cancers in the TCGA SpliceSeq project and 238 558 AS events across 32 cancers in the TCGA SplAdder project. The new version of the database contains several useful features, such as annotation of alternative splicing-associated transcripts, survival analysis based on median and optimal cut-offs, differential analysis between TCGA tumour samples and adjacent normal samples or GTEx normal samples, pan-cancer views of alternative splicing, splicing differences and results of Cox'PH regression, identification of clinical indicator-relevant and cancer-specific splicing events, and downloadable splicing data in the SplAdder project. Overall, the substantially updated version of OncoSplicing (www.oncosplicing.com ) is a user-friendly and registration-free database for browsing and searching clinically relevant alternative splicing in human cancers.